Banana Exports as a Rural Development Strategy in Colombia (2019)
This article seeks to identify opportunities in the international markets for fresh and processed Colombian plantain, from the analysis of the information obtained from secondary sources in which the consumption variables, production statistics, exports and imports, regulations, restrictions and technical requirements are analyzed for the period 2013-2017, to which the classification criteria of the Uppsala and Vernon models are applied. We identify products with higher demand and the countries with higher probability of access, as a proposal for their incorporation into the competitive strategy for plantain producers and companies in Colombia. The study concludes that the fresh and processed products such as frozen plantain, chips and plantain flour present a significant demand, which can be marketed with better results in the US and European markets.